P597 Optimising therapeutic drug monitoring of adalimumab with dried blood samples in IBD patients: an interim analysis. (25th January 2019) - Berends, S; Bloem, K; Talwar, R; De Vries, A; Schaap, T; Strik, A; Löwenberg, M; D'Haens, G; Mathôt, R
Abstract: Background: Therapeutic drug monitoring (TDM) can optimise the efficacy of adalimumab (ADL) in patients with inflammatory bowel disease (IBD). Capillary blood obtained via finger prick (i.e. dried blood samples (DBS)) can be used to measure anti-TNF serum concentrations. Patients suspected of loss of response to ADL, can send in a DBS from home to check the serum ADL concentration. Dose adjustments for a patient can then be made without coming to the hospital first. We compared ADL serum concentrations and ADL concentrations measured by DBS in IBD patients. Methods: IBD patients, receiving ADL therapy, were prospectively enrolled during a scheduled routine visit to the outpatient clinic. From each patient, blood was obtained via venepuncture and via DBS. Capillary blood for DBS was obtained with a Mitra microsampling device. Serum and DBS ADL concentrations were measured using an ELISA (Sanquin, the Netherlands) with lower limit of quantification (LLOQ) of 0.01 mg/l. A fixed haematocrit (Hct) value of 0.42 was used to convert DBS eluate results to values which can be compared with (venous) serum concentrations. Pearson's correlation coefficient was used to assess correlation between venepuncture and DBS results, and Passing-Bablok regression was performed. Results: Thirty-three patients (Crohn's disease: 27, ulcerative colitis: 6) were evaluated in this interim analysis. Thirty-one patients received ADL maintenance treatment. One patient was excluded because ADL concentrations were below LLOQ by using either DBS or venous blood (with detectable anti-ADL antibodies). Median [interquartile range (IQR)] albumin and CRP were 43 g/l [42–45 g/l] and 1.7 mg/l [0.9–3.9 mg/l], respectively. Samples were obtained after a median [IQR] of 6 [4–10] days after the last ADL administration with a median [IQR] serum ADL concentration of 5.1 [8.3–12.7] mg/l. Patients had a median [IQR] serum Hct of 0.40 L/l [0.42–0.44 L/l]. A high correlation was found between venepuncture and DBS results (Pearson's correlation coefficient: 0.96). Passing-Bablok regression showed no proportional or systematic bias with the intercept of the regression line including zero (0.84 mg/l (95% CI -0.08–1.56 mg/l)) and the slope including 1 (0.89 (95% CI 0.79–1.01)). Conclusions: DBS via finger prick can be used for the assessment of serum ADL concentrations. This method can facilitate broader use of TDM in the treatment of IBD patients using ADL.